Interacting Regulatory Circuits Involved in Orderly Control of Photosynthesis Gene Expression in Rhodobacter sphaeroides 2.4.1 - Oh, Jeong-Il (American Society for Microbiology, 2000)
FnrL, the homolog of the global anaerobic regulator Fnr, is required for the induction of the photosynthetic apparatus in Rhodobacter sphaeroides 2.4.1. Thus, the precise role of FnrL in photosynthesis (PS) gene expression and its interaction(s) with other regulators of PS gene expression are of considerable importance to our understanding of the regulatory circuitry governing spectral complex formation. Using a CcoP and FnrL double mutant strain, we obtained results which suggested that FnrL is not involved in the transduction of the inhibitory signal, by which PS gene expression is “silenced,” emanating from the cbb(3) oxidase encoded by the ccoNOQP operon under aerobic conditions. The dominant effect of the ccoP mutation in the FnrL mutant strain with respect to spectral complex formation under aerobic conditions and restoration of a PS-positive phenotype suggested that inactivation of the cbb(3) oxidase to some extent bypasses the requirement for FnrL in the formation of spectral complexes. Additional analyses revealed that anaerobic induction of the bchE, hemN, and hemZ genes, which are involved in the tetrapyrrole biosynthetic pathways, requires FnrL. Thus, FnrL appears to be involved at multiple loci involved in the regulation of PS gene expression. Additionally, bchE was also shown to be regulated by the PrrBA two-component system, in conjunction with hemN and hemZ. These and other results to be discussed permit us to more accurately describe the role of FnrL as well as the interactions between the FnrL, PrrBA, and other regulatory circuits in the regulation of PS gene expression.